Near-infrared sulfide fluorescent material with ultra-long emission wavelength and preparation method thereof
Through the ZnGa2-2xCr2xS4 material replaced by Ga3+ ions with Cr4+ ions, the problem of insufficient efficiency and stability of the near-infrared second-zone broadband emission fluorescent materials in the prior art is solved, and efficient and stable near-infrared second-zone broadband emission is achieved, which is suitable for the field of near-infrared spectroscopy technology.
Patent Information
- Application Number
- CN202411806199.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-14
AI Technical Summary
It is difficult for the prior art to develop highly efficient, stable, and color purity near infrared second-zone broadband emission fluorescent materials, especially in the range of emission wavelengths of 1000 to 1700 nm. The emission efficiency and stability of the existing materials are insufficient, which limits their application in the field of near infrared spectroscopy technology.
Using the chemical formula of ZnGa2-2xCr2xS4, a near-infrared sulfide fluorescent material with an ultra-long emission wavelength was prepared by substituting Ga3+ ions with Cr4+ ions. The material produces near-infrared second-zone broadband emission with a half-maximum width of 200 nm under illumination of a light source of 590 nm, with the optimal emission wavelength at 1490 nm.
It has achieved efficient and stable near-infrared second-zone broadband emission, and the material has good physical and chemical stability. It is suitable for near-infrared spectroscopy technology fields, such as biometrics, non-invasive monitoring, food analysis and environmental detection.
Smart Images

Figure CN119614193A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fluorescent materials, and in particular relates to a near-infrared sulfide fluorescent material with an ultra-long emission wavelength and a preparation method thereof. Background Art
[0002] Near-infrared light has the advantages of low energy and strong penetration, making near-infrared spectroscopy technology a combination of fast detection speed, non-destructive, and real-time. It has attracted more and more attention and has great application prospects in the fields of detection and analysis, biological imaging, night vision lighting, modern agriculture, and machine vision. Commonly used near-infrared light sources on the market mainly include incandescent lamps, halogen lamps, fluorescent lamps, short-wave infrared lasers, and infrared light-emitting diodes, but they all have inherent defects. Among them, incandescent lamps and halogen lamps are large in size, high in energy consumption, low in efficiency, and short in service life; fluorescent lamps are inefficient, contain heavy metal elements, and are prone to flickering; short-wave infrared lasers have a small divergence angle, high power consumption, and relatively high cost; infrared light-emitting diodes have a narrow emission band, poor thermal stability, and high production equipment costs, and cannot be widely used in the field of near-infrared spectroscopy technology.
[0003] However, the emission of existing high-efficiency near-infrared emission systems is mainly concentrated in the band less than 1000nm, and there is still a lack of efficient long-wave emission systems. At the same time, food component detection, industrial or scientific research spectral analysis systems all require continuous near-infrared light sources with as wide a spectrum as possible, but when the emission band of existing near-infrared phosphors red-shifts or broadens to long waves, it is often accompanied by a sharp attenuation of luminous efficiency, which greatly affects the development of the above research.
[0004] Compared with the near infrared region I (NIR-I, 700-1000nm) band, the near infrared region II (NIR-II, 1000-1700nm) spectrum has low scattering in vivo, deep tissue penetration and high imaging resolution, and therefore shows important application prospects in multidisciplinary cross-fields such as analytical chemistry, biology and clinical medicine. Therefore, obtaining fluorescent materials that can emit near-infrared light has always been a hot topic in this field, especially when it comes to near infrared region II applications, it is necessary to develop region II near-infrared fluorescent materials with a main emission wavelength peak at 1000-1700nm. The prior art (Hong Xuechuan, Xiao Yuling, Zeng Xiaodong, Lin Jiacheng, CN109336909B, Near-infrared zone II fluorescent compound with aggregation-induced emission properties and preparation method, nanoparticle micelle and application thereof) discloses an organic small molecule compound that can produce near-infrared zone II luminescence, but due to the unstable chemical properties of organic matter, the service life after being encapsulated in a near-infrared device is short; the prior art (Fan Quli, Wang Qi, Xu Jingzeng, Xia Bing, Lu Feng, Huang Wei, CN108864106B, Preparation and application of near-infrared zone II organic small molecule fluorescent probe) also discloses a near-infrared zone II organic small molecule, whose main component is a diketopyrrolidine (DPP) derivative, but DPP is also an organic matter and also has stability problems.
[0005] Inorganic materials are relatively stable, so stable near-infrared zone II luminescent materials can be found in inorganic materials. The prior art (Peng Guoxin, Li Yang, Zhao Weiren, Dou Xiaojing, Lin Xiaohui, CN 110028958 A, a near-infrared sulfide long afterglow luminescent material, preparation method and application thereof) discloses a near-infrared sulfide long afterglow luminescent material, with ZnGa2S4 as the matrix, and 0.1-5.0 mol% of Cr2O3 is doped in the matrix, but the material calcination temperature is 1100-1200℃, and the luminescence peak is at 740nm, and the emission spectrum of the near-infrared zone II is not realized; the prior art (Yang Huanghao, Hong Zhongzhu, Chen Qiushui, CN112480925B, near-infrared zone II luminescent long afterglow nanoprobe based on x-ray excitation, preparation method and application in in vivo imaging analysis) also discloses a chemical formula of NaLu 0.8 F4:Gd 0.2-x / LnX@NaReF4, near-infrared second-zone luminescent material based on X-ray excitation, where Ln is selected from Ho 3+ , Er 3+ 、Tm 3+ or Yb 3+ ;Re is selected from Lu 3+ Under the excitation of X-rays, this material will produce 900~1600nm range, all from Ho 3+ , Er 3+ 、Tm 3+ or Yb 3+The ff transition of the near-infrared region II fluorescence emission, but it should be pointed out that the characteristic of the ff transition is that the emission spectrum is a linear spectrum, and the half-height width of the spectrum is only a few nanometers, which cannot cover the near-infrared region II on a large scale. The packaged near-infrared device will not produce a wide-spectrum near-infrared region II emission, so its application is inevitably limited; the prior art (Zhu Haomiao, Wu Luyan, Lin Yaling, CN114250073A, a nanomaterial with long afterglow luminescence in the near-infrared and its preparation method and application) also discloses a near-infrared fluorescent material that can produce near-infrared region II emission, and its corresponding chemical formula is A3Al x Ga y O 12 :aM 3+ / bLn 3+ / cCe 3+ ; Among them, M 3+ , Ln 3+ 、Ce 3+ is the luminescence center, A is at least one of Y, La, Lu, Ho or Gd; M is at least one of Cr, V or Yb; Ln is at least one of the rare earth elements Er, Nd, Ho, Tm, Pr or Sm; 0 ≤ x ≤ 5, 0 ≤ y ≤ 5, and x+y=5; 0mol% ≤ a ≤5mol%; 0.01mol% ≤ b ≤ 20mol%; 0.01mol% ≤ c ≤ 10mol%, but it should be pointed out that although the material is doped with Cr 3+ , but Cr 3+ The near-infrared emission generated is the near-infrared zone I, and all the near-infrared zone II fluorescence emissions of the material come from the ff transition of Er, Nd, Ho, Tm, Pr or Sm, which still limits its application; the prior art (Liu Xiaolong, Wang Peiyuan, Wu Ming, Li Jiaqi, Li Yang, Lin Jinyan, Luo Qiang, CN113927027B, a virus-like hollow manganese oxide loaded near-infrared zone II b-excited rare earth nanocrystals and its preparation method and application) also discloses a virus-like hollow oxide loaded near-infrared zone II fluorescent material with a chemical formula of NaErF4:2%Ho@NaYF4. Obviously, all the near-infrared zone II fluorescence emissions of the material come from the ff transition of Er and Ho, which limits its application.
[0006] Cr 3+ The emission of the ions comes from the Cr 3+ of 4 T2 energy level, therefore, its luminescence is greatly affected by the crystal field. In some material systems, such as Al2O3:Cr 3+(Prior Art, Geeta Rani, PD Sahare, Structural and photoluminescent properties of Al2O3:Cr 3+ nanoparticles via solution combustion synthesis method, Advanced Powder Technology, 2014, VOL 25:767-772), whose emission spectrum is very narrow (the half-width is only a few nm); but in some other material systems, such as La3GaGe5O 16 :Cr 3+ (Prior Art, Shaoan Zhang, Yihua Hu, Li Chen, La3GaGe5O 16 :Cr 3+ phosphor: the near-infrared persistent luminescence, Optical MaterialsExpress, 2016, VOL 6:1247), Cr 3+ It will also show an ultra-wide emission spectrum. Obviously, Cr 3+ The luminescence of Cr is obviously unpredictable. In addition, due to the forbidden transition caused by dd parity, 3+ It is usually difficult to achieve emission with excellent thermal stability and quantum efficiency with doped near-infrared phosphors, such as Ca3Sc2Si3O 12 :Cr 3+ (Prior art, Zhenwei, Jia, et al. Strategies to approach high performance in Cr 3+ -doped phosphors for high-power NIR-LED light sources, Light: Science & Applications, 2020, VOL 9:86) has high thermal stability, but its external quantum efficiency is only 15.5%, and the emission peak is near the short wavelength of 800nm, which cannot reach the long-wavelength near-infrared range; another example is Ca2LuZr2Al3O 12 :Cr 3+(Prior art, Jingnan Zhang, Liangliang Zhang, Smaller stokes shift induced highly efficient broadband near infrared garnet phosphor, Laser & Photonics Reviews 2023, VOL 17: 2200586) Although higher quantum efficiency was achieved by replacing Ca-Zr with Lu-Al, its poor thermal stability limits its further application.
[0007] In addition, the prior art (Jiao Huan, Wang Cuiping, Zhou Yang, Wang Xiaoming, Xu Ling, CN110093155A, a near-infrared second-zone broadband emission phosphor and its preparation method) discloses a phosphor with a chemical formula of M 1+y N y R 2-2y O4:zCr 3+ / xNi 2+ A near-infrared second-zone broadband emission phosphor, wherein M is one or more of Zn, Mg, and Ca elements, N is one or more of Sn, Ge, and Si elements, R is one or more of Ga, Al, and Sc elements, 0≤y≤1, 0≤z≤0.3, and 0≤x≤0.02. Although the phosphor can produce Ni 2+ The emission in the near-infrared region II, but Ni 2+ The absorption of light is poor, so the quantum efficiency of this fluorescent material is not high. When it is used in light-emitting devices that emit near-infrared region II, it is difficult to generate strong energy output in the near-infrared region II.
[0008] The prior art (Zhou Tianliang, Yin Mei, Wang Xudong, Zhao Yulei, Xie Rongjun, CN117384633A, A near-infrared luminescent material with ultra-long emission wavelength) discloses a chemical formula of La4Mg 1-x Cr x B2O 10+0.5x The near-infrared second zone broadband emission phosphor, where 0<x<0.2, can produce 3+ The emission in the near-infrared region II, but the main peak of its emission spectrum is near 1290nm, Cr 3+ It is extremely sensitive to the distortion of crystal field strength and can only have efficient near-infrared emission in highly symmetric structures, which limits its further application.
[0009] Cr 4+ Because of 3 T2→ 3 The electronic transition characteristics of A2 are a promising near-infrared luminescence center in the wavelength range of 1100~1700nm.4+ The doped material exhibits single-peak emission, which is practical, convenient, accurate and reliable, and is more suitable for temperature information labeling; on the other hand, the molecular overtones and stretching vibrations of O─H bonds, C─H bonds and N─H bonds can trigger characteristic absorption in the near-infrared second region; in addition, functional groups are the basic units of organisms, which means that near-infrared luminescence has great potential for non-invasive ingredient detection in food analysis and agriculture.
[0010] Therefore, there is an urgent need to develop a stable, efficient, and color-pure fluorescent material with ultra-long emission wavelength near-infrared emission. Summary of the invention
[0011] The purpose of the embodiments of the present invention is to provide a near-infrared sulfide fluorescent material with an ultra-long emission wavelength, aiming to solve the problems raised in the above background technology.
[0012] The embodiment of the present invention is implemented as follows: a near-infrared sulfide fluorescent material with an ultra-long emission wavelength, the chemical formula of the fluorescent material is ZnGa 2-2x Cr 2x S4, where 0.02≤x≤0.20.
[0013] Another object of the embodiment of the present invention is to provide a method for preparing a near-infrared sulfide fluorescent material with an ultra-long emission wavelength, comprising the following steps: According to the chemical formula ZnGa 2-2x Cr 2x S4, weighing raw materials according to the molar ratio of each element Zn:Ga:Cr=1:2-2x:2x, x is 0.02≤x≤0.20, and the raw materials are compounds containing Zn, Ga, and Cr elements; The weighed raw materials are added with a dispersant and fully ground until a uniform white powder is obtained. The ground white powder is pre-calcined at 650-750°C for 2-3 hours, and then a sulfiding gas is introduced, and then the powder is calcined at 850-950°C for 2-4 hours. The powder is then slowly cooled to room temperature until it cools down to obtain the near-infrared sulfide fluorescent material with an ultra-long emission wavelength.
[0014] Preferably, the compound containing the Zn element is any one of ZnO, Zn(OH)2, ZnCl2, and ZnS.
[0015] Preferably, the compound containing Ga element is any one of Ga2O3, Ga(OH)3, GaCl3, and Ga2S3.
[0016] Preferably, the compound containing Cr element is any one of Cr2O3, CrCl2, and Cr2(SO4)3·xH2O.
[0017] Preferably, the dispersant is anhydrous ethanol.
[0018] Another object of an embodiment of the present invention is to provide a near-infrared sulfide fluorescent material with an ultra-long emission wavelength for use in any of the fields of biometrics, non-invasive monitoring, food analysis and environmental testing. An embodiment of the present invention provides a near-infrared sulfide fluorescent material ZnGa with ultra-long emission wavelength 2- 2x Cr 2x S4, Ga in the chemical formula 3+ Cr 4+ Ion substitution, with Cr 4+ Ion substitution Ga 3+ The concentration quenching phenomenon occurs in the process of ions, and it can be effectively excited by blue light and yellow light at the same time, and the optimal emission wavelength is located at 1490nm, which comes from Cr 4+ of 3 T2→ 3 The electronic transition of A2 produces broadband emission in the second region of near-infrared with a half-peak width of 200nm under irradiation of a 590nm light source; The preparation method provided in the embodiment of the present invention uses abundant raw material resources, is simple, easy to operate, low cost, has good physicochemical stability, ideal fluorescence lifetime, is green and pollution-free, has strong applicability, and has a wide emission bandwidth and wavelength. It can be used to prepare high-performance near-infrared pc-LEDs devices and is widely used in the field of near-infrared spectroscopy technology, such as biometrics, non-invasive monitoring, food analysis, and environmental testing. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 The XRD patterns of the materials prepared in Comparative Examples 1-5 of the present invention; Figure 2 XRD patterns of materials prepared in Examples 1-8 and Comparative Example 3 of the present invention; Figure 3 This is the excitation spectrum of the material prepared in Examples 1-8 of the present invention; Figure 4 This is an emission spectrum of the material prepared in Examples 1-8 of the present invention under 590nm excitation; Figure 5 This is the emission spectrum of the material prepared in Example 5 of the present invention under 590nm excitation. DETAILED DESCRIPTION
[0020] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0021] A near-infrared sulfide fluorescent material with an ultra-long emission wavelength, the preparation method of which comprises the following steps: (1) According to the chemical formula ZnGa 2-2x Cr 2x S4, accurately weighing the corresponding raw materials using an electronic balance according to the molar ratio of each element Zn:Ga:Cr=1:2-2x:2x, x is 0.02≤x≤0.20, wherein the raw materials are Zn source, Ga source, and Cr source respectively; The Zn source is an oxide containing Zn or a compound that can be converted into the oxide; The Ga source is an oxide containing Ga or a compound that can be converted into the oxide; The Cr source is an oxide containing Cr or a compound that can be converted into the oxide; (2) The weighed raw materials are placed in an agate mortar, anhydrous ethanol is added as a dispersant, and the raw materials are fully ground until the alcohol evaporates to obtain a uniform white powder. The ground white powder is placed in an alumina crucible, and the crucible is placed in a 600-700°C tubular furnace for pre-burning for 2-3 hours. The crucible is then moved to a 750-950°C tubular furnace and sulfiding gas is introduced. The crucible is fired in a sulfiding environment for 2-4 hours, and then slowly cooled to room temperature until cooled to obtain the near-infrared sulfide fluorescent material.
[0022] The specific implementation of the present invention is described in detail below in conjunction with specific embodiments.
[0023] Embodiment 1: A near-infrared sulfide fluorescent material with an ultra-long emission wavelength, wherein the preparation method thereof comprises the following steps: (1) According to the chemical formula ZnGa 2-2x Cr 2x S4 (x=0.02), the initial raw materials are ZnO, Ga2O3, and Cr2O3 accurately weighed according to the stoichiometric ratio, and an appropriate amount of anhydrous ethanol is added as a dispersant to fully grind for 30 minutes to mix the raw materials evenly to obtain a mixed powder; (2) Place the mixed powder into an alumina crucible, pre-sinter the crucible in a 700°C tubular furnace for 2 h, then move the crucible to an 850°C tubular furnace and introduce sulfide gas CS2 for 4 h, then slowly cool to room temperature until cooled.
[0024] Embodiment 2: A near-infrared sulfide fluorescent material with an ultra-long emission wavelength, the preparation method of which comprises the following steps: (1) According to the chemical formula ZnGa 2-2x Cr 2x S4 (x=0.04), the initial raw materials are ZnO, Ga2O3, and Cr2O3 accurately weighed according to the stoichiometric ratio, and an appropriate amount of anhydrous ethanol is added as a dispersant to fully grind for 30 minutes to make the raw materials evenly mixed to obtain a mixed powder; (2) Place the mixed powder into an alumina crucible, pre-sinter the crucible in a 700°C tubular furnace for 2 h, then move the crucible to an 850°C tubular furnace and introduce sulfide gas CS2 for 4 h, then slowly cool to room temperature until cooled.
[0025] Embodiment 3: A near-infrared sulfide fluorescent material with ultra-long emission wavelength, the preparation method of which comprises the following steps: (1) According to the chemical formula ZnGa 2-2x Cr 2x S4 (x=0.06), the initial raw materials are ZnO, Ga2O3, and Cr2O3 accurately weighed according to the stoichiometric ratio, and an appropriate amount of anhydrous ethanol is added as a dispersant to fully grind for 30 minutes to mix the raw materials evenly to obtain a mixed powder; (2) Place the mixed powder into an alumina crucible, pre-sinter the crucible in a 700°C tubular furnace for 2 h, then move the crucible to an 850°C tubular furnace and introduce sulfide gas CS2 for 4 h, then slowly cool to room temperature until cooled.
[0026] Embodiment 4: A near-infrared sulfide fluorescent material with an ultra-long emission wavelength, the preparation method of which comprises the following steps: (1) According to the chemical formula ZnGa 2-2x Cr 2x S4 (x=0.08), the initial raw materials are ZnO, Ga2O3, and Cr2O3 accurately weighed according to the stoichiometric ratio, and an appropriate amount of anhydrous ethanol is added as a dispersant to fully grind for 30 minutes to mix the raw materials evenly to obtain a mixed powder; (2) Place the mixed powder into an alumina crucible, pre-sinter the crucible in a 700°C tubular furnace for 2 h, then move the crucible to an 850°C tubular furnace and introduce sulfide gas CS2 for 4 h, then slowly cool to room temperature until cooled.
[0027] Embodiment 5: A near-infrared sulfide fluorescent material with an ultra-long emission wavelength, the preparation method of which comprises the following steps: (1) According to the chemical formula ZnGa 2-2x Cr 2xS4 (x = 0.10), the initial raw materials are ZnO, Ga2O3, and Cr2O3 accurately weighed according to the stoichiometric ratio, and an appropriate amount of anhydrous ethanol is added as a dispersant to fully grind for 30 minutes to mix the raw materials evenly to obtain a mixed powder; (2) Place the mixed powder into an alumina crucible, pre-sinter the crucible in a 700°C tubular furnace for 2 h, then move the crucible to an 850°C tubular furnace and introduce sulfide gas CS2 for 4 h, then slowly cool to room temperature until cooled.
[0028] Embodiment 6: A near-infrared sulfide fluorescent material with an ultra-long emission wavelength, the preparation method of which comprises the following steps: (1) According to the chemical formula ZnGa 2-2x Cr 2x S4 (x=0.14), the initial raw materials are ZnO, Ga2O3, and Cr2O3 accurately weighed according to the stoichiometric ratio, and an appropriate amount of anhydrous ethanol is added as a dispersant to fully grind for 30 minutes to mix the raw materials evenly to obtain a mixed powder; (2) Place the mixed powder into an alumina crucible, pre-sinter the crucible in a 700°C tubular furnace for 2 h, then move the crucible to an 850°C tubular furnace and introduce sulfide gas CS2 for 4 h, then slowly cool to room temperature until cooled.
[0029] Embodiment 7: A near-infrared sulfide fluorescent material with an ultra-long emission wavelength, the preparation method of which comprises the following steps: (1) According to the chemical formula ZnGa 2-2x Cr 2x S4 (x=0.16), the initial raw materials are ZnO, Ga2O3, and Cr2O3 accurately weighed according to the stoichiometric ratio, and an appropriate amount of anhydrous ethanol is added as a dispersant to fully grind for 30 minutes to make the raw materials evenly mixed to obtain a mixed powder; (2) Place the mixed powder into an alumina crucible, pre-sinter the crucible in a 700°C tubular furnace for 2 h, then move the crucible to an 850°C tubular furnace and introduce sulfide gas CS2 for 4 h, then slowly cool to room temperature until cooled.
[0030] Embodiment 8: A near-infrared sulfide fluorescent material with an ultra-long emission wavelength, the preparation method of which comprises the following steps: (1) According to the chemical formula ZnGa 2-2x Cr 2x S4 (x=0.20), the initial raw materials are ZnO, Ga2O3, and Cr2O3 accurately weighed according to the stoichiometric ratio, and an appropriate amount of anhydrous ethanol is added as a dispersant to fully grind for 30 minutes to make the raw materials evenly mixed to obtain a mixed powder; (2) Place the mixed powder into an alumina crucible, pre-sinter the crucible in a 700°C tubular furnace for 2 h, then move the crucible to an 850°C tubular furnace and introduce sulfide gas CS2 for 4 h, then slowly cool to room temperature until cooled.
[0031] Comparative Example 1: A near-infrared sulfide fluorescent material, the preparation method of which comprises the following steps: (1) According to the chemical formula ZnGa 2-2x Cr 2x S4 (x=0), the initial raw materials are ZnO, Ga2O3, and Cr2O3 accurately weighed according to the stoichiometric ratio, and an appropriate amount of anhydrous ethanol is added as a dispersant to fully grind for 30 minutes to make the raw materials evenly mixed to obtain a mixed powder; (2) Place the mixed powder into an alumina crucible, pre-sinter the crucible in a 700°C tubular furnace for 2 h, then move the crucible to a 750°C tubular furnace and introduce sulfide gas CS2 for 4 h, then slowly cool to room temperature until cooled.
[0032] Comparative Example 2: A near-infrared sulfide fluorescent material, the preparation method of which comprises the following steps: (1) According to the chemical formula ZnGa 2-2x Cr 2x S4 (x=0), the initial raw materials are ZnO, Ga2O3, and Cr2O3 accurately weighed according to the stoichiometric ratio, and an appropriate amount of anhydrous ethanol is added as a dispersant to fully grind for 30 minutes to make the raw materials evenly mixed to obtain a mixed powder; (2) Place the mixed powder into an alumina crucible, pre-sinter the crucible in a 700°C tubular furnace for 2 h, then move the crucible to an 800°C tubular furnace and introduce sulfide gas CS2 for 4 h, then slowly cool to room temperature until cooled.
[0033] Comparative Example 3: A near-infrared sulfide fluorescent material, the preparation method of which comprises the following steps: (1) According to the chemical formula ZnGa 2-2x Cr 2x S4 (x=0), the initial raw materials are ZnO, Ga2O3, and Cr2O3 accurately weighed according to the stoichiometric ratio, and an appropriate amount of anhydrous ethanol is added as a dispersant to fully grind for 30 minutes to make the raw materials evenly mixed to obtain a mixed powder; (2) Place the mixed powder into an alumina crucible, pre-sinter the crucible in a 700°C tubular furnace for 2 h, then move the crucible to an 850°C tubular furnace and introduce sulfide gas CS2 for 4 h, then slowly cool to room temperature until cooled.
[0034] Comparative Example 4: A near-infrared sulfide fluorescent material, the preparation method of which comprises the following steps: (1) According to the chemical formula ZnGa 2-2x Cr 2x S4 (x=0), the initial raw materials are ZnO, Ga2O3, and Cr2O3 accurately weighed according to the stoichiometric ratio, and an appropriate amount of anhydrous ethanol is added as a dispersant to fully grind for 30 minutes to make the raw materials evenly mixed to obtain a mixed powder; (2) Place the mixed powder into an alumina crucible, pre-sinter the crucible in a 700°C tubular furnace for 2 hours, then move the crucible to a 900°C tubular furnace and introduce sulfide gas CS2 for 4 hours, then slowly cool to room temperature until cooled.
[0035] Comparative Example 5: A near-infrared sulfide fluorescent material, the preparation method of which comprises the following steps: (1) According to the chemical formula ZnGa 2-2x Cr 2x S4 (x=0), the initial raw materials are ZnO, Ga2O3, and Cr2O3 accurately weighed according to the stoichiometric ratio, and an appropriate amount of anhydrous ethanol is added as a dispersant to fully grind for 30 minutes to make the raw materials evenly mixed to obtain a mixed powder; (2) Place the mixed powder into an alumina crucible, pre-sinter the crucible in a 700°C tubular furnace for 2 hours, then move the crucible to a 950°C tubular furnace and introduce sulfide gas CS2 for 4 hours, then slowly cool to room temperature until cooled.
[0036] Performance Testing: The materials prepared in Comparative Examples 1-5 were analyzed using powder X-ray diffraction (XRD) technology to obtain XRD patterns as shown in Figure 1 As shown, according to Figure 1 It can be seen that during the preparation process, the firing temperature was 850 °C with good phase; The materials prepared in Examples 1-8 and Comparative Example 3 were analyzed to obtain XRD patterns as shown in Figure 2 As shown, according to Figure 2 It can be seen that the samples introduced different concentrations of Cr 4+ After addition, the phase can still maintain the purity of the undoped phase, indicating that the material has a suitable crystal structure and can be introduced with doped ions to achieve ultra-far and near-infrared luminescence, which has great application potential in the near-infrared field. Figure 3 and Figure 4The emission spectra and excitation spectra of the materials prepared in Examples 1-8 are shown respectively. It can be seen that the excitation spectrum of the material under 1490nm near-infrared monitoring shows a linear excitation peak in the range of 300-900nm, and there is a strong excitation near 590nm, indicating that it can be applied to pc-LEDs excited by near-ultraviolet and blue light LED chips. Under 590nm excitation, the material shows broadband near-infrared emission, ranging from 1250nm to 1650nm, and the main emission peak wavelength is near 1490nm. ZnGa 2-2x Cr 2x S4 (x = 0), i.e., ZnGa2S4, has no emission signal response under 590nm excitation, indicating that the material has no near-infrared luminescence; Figure 5 The optimal emission wavelength and half-peak width in the emission spectrum of the material prepared in Example 5 show that the material exhibits broadband emission in the near-infrared region II under 590nm excitation, with a half-peak width of 200nm and an optimal emission wavelength of 1490nm. The results show that the material prepared in the embodiment of the present invention can be widely used in the field of near-infrared spectroscopy technology.
[0037] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A near-infrared sulfide fluorescent material with ultra-long emission wavelength, characterized in that: The chemical formula of the fluorescent material is ZnGa 2-2x Cr 2x S4, where 0.02≤x≤0.
20.
2. A method for preparing the near-infrared sulfide fluorescent material with ultra-long emission wavelength as claimed in claim 1, characterized in that: The following steps are involved: According to the chemical formula ZnGa 2-2x Cr 2x S4, weighing raw materials according to the molar ratio of each element Zn:Ga:Cr=1:2-2x:2x, x is 0.02≤x≤0.20, and the raw materials are compounds containing Zn, Ga, and Cr elements; The weighed raw materials are added with a dispersant and fully ground until a uniform white powder is obtained. The ground white powder is pre-calcined at 650-750°C for 2-3 hours, and then a sulfiding gas is introduced, and then the powder is calcined at 850-950°C for 2-4 hours. The powder is then slowly cooled to room temperature until it cools down to obtain the near-infrared sulfide fluorescent material with an ultra-long emission wavelength.
3. The method for preparing the near-infrared sulfide fluorescent material with ultra-long emission wavelength according to claim 2, characterized in that: The compound containing the Zn element is any one of ZnO, Zn(OH)2, ZnCl2, and ZnS.
4. The method for preparing the near-infrared sulfide fluorescent material with ultra-long emission wavelength according to claim 2, characterized in that: The compound containing Ga element is any one of Ga2O3, Ga(OH)3, GaCl3, and Ga2S3.
5. The method for preparing the near-infrared sulfide fluorescent material with ultra-long emission wavelength according to claim 2, characterized in that: The compound containing Cr element is any one of Cr2O3, CrCl2, and Cr2(SO4)3·xH2O.
6. The method for preparing the near-infrared sulfide fluorescent material with ultra-long emission wavelength according to claim 2, characterized in that: The dispersant is anhydrous ethanol.
7. An application of the near-infrared sulfide fluorescent material with ultra-long emission wavelength as claimed in claim 1 in any field of bio-recognition, non-invasive monitoring, food analysis and environmental detection.
Citation Information
Patent Citations
Near-infrared sulfide long-afterglow luminescent material as well as preparation method and application thereof
CN110028958A
Broadband near-infrared fluorescent powder based on spinel structure and preparation method and application thereof
CN114507517A
Oxide phosphor, light-emitting device, and method for producing oxide phosphor
US20240263070A1
Cited By
A broadband near-infrared sulfide fluorescent powder with an olivine structure and a preparation method and application thereof
CN122726910A